Long-term topical corticosteroid use and altered facial melasma patterns: a retrospective cohort study - Jesmin, Saymun; Shamim, Sarker M. A.; Shumi, Farhana R.; Sharmin, Shumana; Shoma, Rabeya A.; Hafiz, Shamma B.; Bipasha, Tasnuva (International Journal of Research in Dermatology, 2025)
Background: Melasma is a common acquired hyperpigmentation disorder primarily affecting the face. Topical corticosteroids are frequently used, often unsupervised, in melasma management but may induce alteration in pigmentation patterns and adverse sequelae. This study aimed to evaluate the impact of long-term topical corticosteroid use on facial melasma pattern alterations and associated pigmentary sequelae in affected patients. Methods: A retrospective cohort study was conducted involving 60 patients diagnosed with facial melasma who had a history of prolonged topical corticosteroid use. Baseline demographic and clinical data, corticosteroid usage patterns, changes in melasma distribution, pigmentary sequelae, and clinical outcomes following corticosteroid discontinuation were collected and analyzed descriptively. Results: The majority were female (n=52, 86.7%) with a mean age of 39.7±9.2 years. Following prolonged steroid exposure, a pigmentary pattern shift was observed in all participants: 40 (66.7%) developed a centrofacial pattern and 16 (26.7%) exhibited a mixed pattern. Post-inflammatory hyperpigmentation (PIH) was noted in 100% of cases. Despite subsequent dermatological treatment and cessation of TCS use, 48 patients (80.0%) reported no clinical improvement, and 52 (86.7%) showed no visible recovery at their final follow-up assessment. Conclusion: Prolonged topical corticosteroid use in melasma patients is strongly associated with significant alteration in melasma distribution and persistent pigmentary sequelae, highlighting the need for regulated corticosteroid use and increased patient education. Early dermatologic supervision is critical to prevent adverse pigmentary outcomes.